Optimized donor management and organ preservation before kidney transplantation - Mundt, Heiko; Yard, Benito A.; Krämer, Bernhard; Benck, Urs Tobias; Schnülle, Peter (Transplant international, 2016)
Kidney transplantation is a major medical improvement for patients with end-stage renal disease, but organ shortage limits its widespread use. As a consequence, the proportion of grafts procured from extended criteria donors (ECD) has increased considerably, but this comes along with increased rates of delayed graft function (DGF) and a higher incidence of immune-mediated rejection that limits organ and patient survival. Furthermore, most grafts are derived from brain dead organ donors, but the unphysiological state of brain death is associated with significant metabolic, hemodynamic, and pro-inflammatory changes, which further compromise patient and graft survival. Thus, donor interventions to preserve graft quality are fundamental to improve long-term transplantation outcome, but interventions must not harm other potentially transplantable grafts. Several donor pretreatment strategies have provided encouraging results in animal models, but evidence from human studies is sparse, as most clinical evidence is derived from single-center or nonrandomized trials. Furthermore, ethical matters have to be considered especially concerning consent from donors, donor families, and transplant recipients to research in the field of donor treatment. This review provides an overview of clinically proven and promising preclinical strategies of donor treatment to optimize long-term results after kidney transplantation.